Euripides' Kresphontes and Archelaos : introduction, text, and commentary - Harder, Annette. (Mnemosyne, Supplements, 1985)
This book contains an introduction to the text of and a commentary on the fragments of two plays by Euripides, the Kresphontes (ca. 424 B.C.) and the Archelaos (ca. 408/7 B.C.) Fragments of both plays are preserved in quotations by other writers and in recently published papyri. The introduction discusses aspects of the background and of the contents of the plays, such as, for example, their first performances, the relation of the Kresphontes with the plays about Orestes, and Euripides' motives in writing the Archelaos (politics or flattery?). The commentary to each play deals with the interpretation of the fragments and testimonia , with textual problems and with typical elements of Euripides' style. This is the first full-scale treatment of both plays and offers, thanks to modern papyrus finds, some new evidence on their composition and context. The text of the papyrus fragments is based on personal inspection of the papyri concerned, which has resulted in a number of new readings.